Masa Kehamilan dan Persalinan dalam Perspektif Al-Qur’an dan Sains: Kajian Surah Al-Ahqâf Ayat 15 - Aulia, Jannatul; Idham, Ahmad Ridhoni; Kiramy, Salma; Mujahid, Ahmad (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study explores the integration of divine wisdom in the Qur'an with modern scientific findings regarding pregnancy and childbirth, focusing on Surah Al-Ahqâf verse 15. The research aims to analyze the Qur'anic descriptions of pregnancy duration and maternal struggles, correlating them with contemporary embryology and medical science. Using a qualitative method with thematic tafsir (interpretation) analysis, the study examines classical and modern exegeses, such as Tafsir Al-Misbah and Fi Zhilal Al-Qur'an, alongside scientific literature on fetal development and maternal health. The findings reveal a profound alignment between Qur'anic insights and scientific evidence, particularly in the stages of pregnancy, physical and emotional challenges faced by mothers, and the total duration of pregnancy and breastfeeding (30 months). The study underscores the Qur'an's miraculous accuracy in describing biological processes and highlights the ethical imperative to honor maternal sacrifices.